Pain remission following delayed targeted muscle reinnervation in amputees: clinical article - Raasveld, Floris V.; Mayrhofer-Schmid, Maximilian; Johnston, Benjamin R.; Hwang, Charles D.; Valerio, Ian L.; Eberlin, Kyle R. (Microsurgery, 2024)
Introduction Targeted muscle reinnervation (TMR) has demonstrated efficacy for treatment of neuropathic pain. This study aims to identify patients for whom delayed TMR may be most effective and to identify associated factors for favorable pain outcomes in this patient population. Methods An analysis was conducted on prospectively enrolled amputee patients who underwent delayed TMR at a tertiary care center from 2017 to 2024. Data on demographics, comorbidities, surgical details, and pain outcomes were collected. Patient reported pain severity on a 0-10 scale was prospectively collected. The main pain outcome was pain remission (achieving the minimally clinically important difference (MCID)). Additionally, sustained mild pain (pain score ≤ 3/10 for ≥ 3 months), and pain disappearance (pain score 0/10 for ≥ 3 months) were assessed. Multivariable regression analyses identified factors influencing pain outcomes. Results Out of 101 patients included in this study, 64 patients (63.4%) achieved pain remission within a two-year post-operative period, and 37 patients (36.6%) did not. Sustained mild pain, which could be achieved in addition to pain remission, was achieved by 45.8% of patients, with 17.8% of these achieving complete pain disappearance. Patients achieving pain remission demonstrated lower pain over the entire post-operative trajectory (p < 0.001). Lower pre-operative pain scores, absence of depression, no pre-operative opioid use, lower Elixhauser Comorbidity Index, and distal amputation levels were correlated with favorable outcomes following delayed TMR (p < 0.05). Discussion Pre-operative pain severity, psychiatric comorbidities, and opioid use significantly influenced pain outcomes, emphasizing the need for comprehensive patient assessment. These findings will help with patient stratification and pre-operative counseling to support patients who are best suitable for delayed TMR surgery.